La giusta distanza dalle cose. Due opere di Ignazio Gardella - Mugnai, Francesca (Firenze Architettura, 2018)
Ignazio Gardella’s dialogue with history is notoriously at the foundation of his compositional procedure, which is based on the knowledge and assimilation of the features of the place. Taking as examples the Regina Isabella Baths on the Island of Ischia and the Faculty of Architecture in Genoa, this paper attempts to define Gardella’s method as the construction of a distance in which the new is devised as a backdrop available for setting the stage for the representation of the ancient.